The race/color question in the care process in a psychosocial care center for children and adolescents - Bruna de Paula Candido; Sônia Barros; Luciane Régio; Caroline Ballan; Márcia Aparecida Ferreira de Oliveira (SciELO, 2022)
ABSTRACT Objective: To recognize the actions related to race/color developed in the care process of the black child and adolescent population of a Psychosocial Care Center for children and adolescents in Brazil. Method: This is a study with a qualitative approach focusing on the three-dimensional racism framework. Data were collected through active medical records and interviews with reference professionals. The results were categorized and thematized through content analysis and the following themes were found: typology of child violence, identification of racism, the school, access to black culture and representativeness. This study obtained ethical approval. Results: The race/color question in the face of violation of fundamental rights of black children/adolescents contributes to the understanding of racism as a social determinant of mental health. Actions to empower the black population include the insertion of the race-color question as an analytical and procedural category in the Singular Therapeutic Projects, as an integral practice of multiprofessional teams work process. Conclusion: It is necessary to invest persistently in the identification and qualification of actions and systematic discussions to face the psychosocial effects of racism.